Pengaruh Pemberian Edukasi Menggunakan Audio Visual (Video) pada Ibu terhadap Pengetahuan Penanganan Tersedak Balita - Indri Mulyani; Nurul Fatwati Fitriana (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2020)
Choking can result in death if handled inappropriately. The accuracy of handling is based on sufficient knowledge. Lack of knowledge for mothers who have toddlers in handling choking results in mothers under five still wrongly handling choking. To find out the effect of providing education using audio visual (video) to housewives on the knowledge of toddler choking handling, to find out differences in maternal knowledge before and after it is done education using audio visual (video). This study used a pre-experimental design technique with a one group pre-test-post-test design approach. Data collection using a questionnaire and data analysis using the Wilcoxon test. The results showed that the average value of knowledge obtained by 69 respondents before being given audio-visual education (video) was 15.06, with a minimum value of 6 to a maximum of 19, and after being given audio-visual education (video) was 18.00, with a minimum value. 12 maximum 21. The results of bivariate analysis using the Wilcoxon test obtained p value 0.000. In conclusion, there is an effect of providing education using audio visual (video) to housewives on the knowledge of choking handling for toddlers in Pajerukan. It needs to be developed by adding variables and using different research designs and using qualitative research types.Â Keywords: Audio Visual Education (Video), Knowledge, Handling Choking